EFFECTS OF PHYSIOTHERAPEUTIC REHABILITATION PRE AND POST PROSTHETICIZATION IN LOWER LIMBS: A SYSTEMATIZED REVIEW. (Fiep Bulletin - online, 2024)
Introduction:Amputation can be described as the removal of part of a limb, characterized by a multifactorial etiology. We know how difficult it is for those who have lost their lower limbs due to some pathology, especially in terms of mobility. Therefore, physiotherapeutic rehabilitation in advance in amputee patients is extremely important so that their adaptation to the use of prostheses occurs gradually and stabilized, allowing the person to resume their daily activities. Physiotherapeutic interventions in amputees in the pre- and post-prosthetic phases are used in different physiotherapy approaches, however, it is necessary to systematize evidence on protocols for conducting rehabilitation. This study aims to verify and present the effectiveness of methods of rehabilitation. physiotherapeutic treatments in rehabilitation in the pre and post prosthetics phase. Methods:This is a systematized research with documentary, bibliographic characteristics, which is retrospective, descriptive in nature, and aims to characterize the scientific production of physiotherapeutic effects in pre- and post-prosthetic rehabilitation in amputees. The search for online data was carried out in both national and international literature, in the period July 2022, with the following databases being searched Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO ), Medical Literature Analysis and Retrieval System Online (MedLine/PubMed), Biomedical Answers (EMBASE), Virtual Health Library (VHL) and Physiotherapy Evidence Database. The articles were obtained using the following keywords: “amputation”, “physiotherapy”, “pre and post prosthetics”, “prosthesis”, “rehabilitation”, under the Boolean descriptors “and” and “or”. The content of the articles was analyzed using the Physiotherapy Evidence Database (PEDro) scale, an instrument designed by the Australian Physiotherapy Association and renowned worldwide in the area. Results: In the results and outcomes of the selected studies, it was possible to observe that the majority of studies use similar conclusions, showing that amputee patients undergoing physical therapy sessions presented positive results. Conclusion: This study confirms that physiotherapeutic interventions in patients with lower limb amputees enable them to continue their daily life, leisure and work activities, promoting bipedal movement in a functional way with comfort and safety when using a prosthesis. Keywords: Amputation, physiotherapy, pre and post prosthetics, rehabilitation.